Effect of Colostral Period on Cows and She-Camels Colostrum Composition and Immunoglobulin Concentration (Journal of Veterinary Medicine and Animal Production, 2021)
The present study was undertaken to investigate the impact of colostral period on colostrum composition and immunoglobulin (Ig) concentration of cows and she-camels. The study was conducted at two sites, the U. of K. Dairy farm and Tamboul Camel Research Centre (TCRC). Six cows and two she camel, immediately post-partum were selected from the U. of K. Dairy farm, and three post calving she-camels, were chosen from the TCRC.. A total of 66 colostrum samples representing two samples from each animal for the first three colostral days were collected and subjected to chemical analysis, by colostremeter apparatus. The results revealed significant (P
Keywords: Colostral Period; Cows